Revolutionizing elementary disaster prevention education and training via augmented reality-enhanced collaborative learning. (9th March 2022) - Lu, Su-Ju; Lin, Yu-Chiao; Tan, Kim Hua; Liu, Ying-Chieh
In light of a recent spike in natural and man-made disasters, there has been an increase in interest in disaster prevention education and training. The effectiveness of both publicly-funded and voluntarily organized disaster education (DE) has attracted wide attention. More studies are needed to understand the innovative pedagogical practice and the impact of technological advances on disaster learning content development, effectiveness and motivation. This study investigates the application of augmented reality (AR) in DE and training. An AR-enhanced tool named 'disaster-proof warrior' was developed and tested to evaluate its enhancement effect on learning under two collaborative learning modes. A series of quasi-experiments involving 85 elementary school subjects was carried out to assess the learning effectiveness and the subjective reaction in learning motivation. The results showed the AR embedded learning tool is effective in engaging and motivating collaborative team knowledge building. This study adds to the existing literature of AR applications in education and training as well as providing a useful reference for future development and improvement of national DE and training.